Unexpected low genetic variation in the South American hystricognath rodent Lagostomus maximus (Rodentia: Chinchillidae) - Gariboldi, María Constanza (2019)
The South American plains vizcacha, Lagostomus maximus inhabits primarily the Pampean and adjoining Espinal, Monte and Chaquenean regions of Argentina. In order to study the population genetic structure of L. maximus, a fragment of 560 bp of the mitochondrial DNA hypervariable region 1from 90 individuals collected from the 3 subspecies and 8 groups along Argentina was amplified and analyzed. We found 9 haplotypes. The haplotype network did not show an apparent phylogeographical signal. Although low levels of genetic variation were found in all the subspecies and groups analyzed, a radiation of L. maximus would have occurred from the North and Center of the Pampean region toward the rest of its geographic range in Argentina. Low levels of genetic diversity, the existence of a single genetically distinct population in Argentina and changes of its effective size indicate that metapopulation processes and changes in human population dynamics during the late-Holocene were important factors shaping the population genetic structure of L. maximus in Argentina.